The Art of War - Tzu, Sun (Lahore Readings Publishing, 2015)
Sun Tzu's teachings on how to successfully respond to and handle situations of conflict is a must-read for today's business leaders (and politicians, and many others)
Keywords: Military art and science -- War -- China